Fire-resistant tannin–ethylene glycol gels working as rubber springs with tuneable elastic properties. Issue 28 (3rd July 2017) - Delgado-Sánchez, C.; Amaral-Labat, G.; Grishechko, L. I.; Sánchez –Sánchez, A.; Fierro, V.; Pizzi, A.; Celzard, A.
Abstract : Non-flammable, tannin-based gels with tuneable elastic properties acting as rubber springs. Abstract : Fire-resistant elastic materials made from tannin, a natural polyphenol extracted from tree barks, and having the appearance and the consistence of rubber are described. They can be produced in any dimension and with any shape based on a quite simple protocol, only consisting in mixing tannin, water and ethylene glycol, in the presence of a low amount of p -toluene sulphonic acid. After curing at 85 °C in an oven and subsequent drying, black elastic blocks are recovered whose mechanical properties can be easily adjusted from the proportions of the ingredients, especially with the amount of ethylene glycol acting as plasticiser. As a result, materials from extra-soft to hard can be obtained. Their retardant performance towards fire is demonstrated, a well-known feature of phenolic compounds here observed for the first time with an elastic material. Physicochemical analyses are performed and explain the chemistry behind the performances of these new biosourced materials.